Sudden infant death syndrome From pathophysiological prospects - Sawaguchi, Toshiko (Springer Japan, 2014)
Sudden infant death syndrome (SIDS) is characterised by the sudden death of an infant that is not predicted by prior medical history and it is still responsible for a large percentage of infant mortalities. The exact causes have long remained unknown, though some risk factors such as including exposure to tobacco smoke, no breast feeding, and prone sleeping position, have been identified. However an analysis linking neurophysiological and neuropathological aspects in a prospective study of SIDS suggests that one of the causes of SIDS is arousal deficiency. This unique book provides the latest, comprehensive information on SIDS research from epidemiology to physiology.